A Novel Rate-dependent Direct Inverse Preisach Model With Input Iteration for Hysteresis Compensation of Piezoelectric Actuators - Sun, Yutong; Ma, Haifeng; Li, Yangmin; Liu, Zhanqiang; Xiong, Zhenhua (International journal of control, automation, and systems, 2024)
This paper proposes the design and validation of a novel rate-dependent direct inverse Preisach model with input iteration (RDIPMII) dedicated to feedforward compensation of hysteresis nonlinearity in piezoelectric actuators (PEAs). Unlike existing similar works, the proposed RDIPMII avoids deriving the parameters of the inverse compensator from the hysteresis model, and could be directly employed as the inverse compensator. Furthermore, RDIPMII is capable of achieving rate-dependent inverse compensation while reducing the experimental burden in identifying models by the use of newly proposed data expression method (DEM). In addition, by integrating iterative learning control (ILC), RDIPMII accomplishes online input iteration to further suppress the hysteresis effect. The feasibility and efficiency of the presented scheme are demonstrated through experimental investigations conducted on a PEA.